Widespread GLI expression but limited canonical hedgehog signaling restricted to the ductular reaction in human chronic liver disease - Grzelak, C.; Sigglekow, N.; Tirnitz-Parker, Nina; Hamson, E.; Warren, A.; Maneck, B.; Chen, J.; Patkunanathan, B.; Boland, J.; Cheng, R.; Shackel, N.; Seth, D.; et al. (Public Library of Science, 2017)
Canonical Hedgehog (Hh) signaling in vertebrate cells occurs following Smoothened activation/translocation into the primary cilia (Pc), followed by a GLI transcriptional response. Nonetheless, GLI activation can occur independently of the canonical Hh pathway. Using a murine model of liver injury, we previously identified the importance of canonical Hh signaling within the Pc+ liver progenitor cell (LPC) population and noted that SMO-independent, GLI-mediated signals were important in multiple Pc-ve GLI2+ intrahepatic populations. This study extends these observations to human liver tissue, and analyses the effect of GLI inhibition on LPC viability/gene expression. Human donor and cirrhotic liver tissue specimens were evaluated for SHH, GLI2 and Pc expression using immunofluorescence and qRT-PCR. Changes to viability and gene expression in LPCs in vitro were assessed following GLI inhibition. Identification of Pc (as a marker of canonical Hh signaling) in human cirrhosis was predominantly confined to the ductular reaction and LPCs. In contrast, GLI2 was expressed in multiple cell populations including Pc-ve endothelium, hepatocytes, and leukocytes. HSCs/myofibroblasts (gt;99%) expressed GLI2, with only 1.92% displaying Pc. In vitro GLI signals maintained proliferation/viability within LPCs and GLI inhibition affected the expression of genes related to stemness, hepatocyte/biliary differentiation and Hh/Wnt signaling. At least two mechanisms of GLI signaling (Pc/SMOdependent and Pc/SMO-independent) mediate chronic liver disease pathogenesis. This may have significant ramifications for the choice of Hh inhibitor (anti-SMO or anti-GLI) suitable for clinical trials. We also postulate GLI delivers a pro-survival signal to LPCs whilst maintaining stemness.